1989
DOI: 10.1177/0013916589211004
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Environmental Concern

Abstract: Differential support for environmental issues has long provoked the curiosity of researchers. Sociodemographics and political ideology have been the primary focus of much research on the determinants of environmental concern. In light of recent work on environmental paradigms and advanced statistical methodologies, it may be advantageous to reexamine the tenets of this body of work. This study restates the findings of previous studies within a broader causal model, and tests that model using data from a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
293
4
21

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(340 citation statements)
references
References 15 publications
22
293
4
21
Order By: Relevance
“…Likewise, as another large, but contentious body of literature points out, younger individuals tend to value environmental amenities to older individuals [26,27]. Both of those findings show up in our results.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, as another large, but contentious body of literature points out, younger individuals tend to value environmental amenities to older individuals [26,27]. Both of those findings show up in our results.…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that their knowledge, attitudes, and practices towards solid waste recycling were influenced by demographic factors of age, education level, gender and occupation [11]. Another example is that individuals' education level can help to predict pro-environmental behaviours [36]. However, Botetzagias added education, gender, income and age as independent variables into the TPB model and found no significant correlation between pro-environmental behaviour and demographic factors [37].…”
Section: Other Possible Influential Factors On Pro-environmental Intementioning
confidence: 99%
“…Weigel (1977) também encontrou uma relação positiva entre ideologia liberal e CPA, enquanto Ostman e Parker (1987) apontaram que possuir conhecimentos acerca do ambiente e seus problemas era um preditor significativo do comportamento pró-ecológico. Outros autores encontraram relações positivas entre possuir atitudes pró-ambientais e o CPA (Hines, Hungerford & Tomera, 1987) e entre manifestar crenças pró-ambientais e esse comportamento pró-ecológico (Samdahl & Robertson, 1989). Apesar de convincentes, os resultados eram limitados, conseguindo explicar apenas uma pequena fração do CPA.…”
Section: O Poder Explicativo Dos Modelosunclassified